Analisis Perbandingan Kinerja Keuangan Pemerintah Daerah Kota/Kabupaten Di Indonesia Sebelum Dan Setelah Pemekaran - Mengkuningtyas, Yeni; Adib, Noval (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This research aims to explore whether there are financial performance differences of local government before and after region expansion. The financial performance of local government is measured by financial ratio includes financial independence ratio, effectiveness of local revenue ratio, efficiency ratio, accordance of capital expenditure ratio and growth of local revenue ratio. This research population are districts or cities in Indonesia that expanded during 2008. The sample used in this research are 17 regions with purposive sampling methods. The data used in this research is secondary data from The Audit Board of the Republic of Indonesia (BPK RI). The data analysis technique used in this research are financial ratio and t-test (paired sample test). The t-test result shows that there is no significant value of financial independence ratio, effectiveness of local revenue ratio, efficiency ratio, accordance of capital expenditure ratio and growth of local revenue ratio. It can be concluded that there is no difference about the financial performance of local governments before and after region expansion in financial independence, effectiveness of local revenue, efficiency, accordance of capital expenditure and the growth of local revenue. Keywords: financial performance, independence, effectiveness, efficiency, capital expenditure, growth, region expansion, local revenue